Urban Space as Spatial Biography in Anthony De Sa’s Barnacle Love and Kicking the Sky - Caporale-Bizzini, Silvia (Hungarian Journal of English and American Studies, 2021)
Drawing on Michel de Certeau’s insights on spatial practices the essay analyzes two works by Canadian writer Anthony De Sa, Barnacle Love (2008) and its follow-up, Kicking the Sky (2013), and maps the spatial biography of their protagonist and narrator, Antonio Rebelo, from childhood to early adulthood. De Sa’s works are set in Toronto, presented as a city in transition. Both narratives interrelate the protagonist’s story with the spatial setting of Toronto’s Little Portugal and with the cultural issue of emigration. They also delve into the complex urban social reality formed by subalternity, hard work, sexual exploitation, spectral memory, and family affects. De Sa’s interpretation of Toronto as the background of Antonio’s spatial biography constructs a complex interaction with the cityscape and its different emotionally conflicting spaces. To greater or lesser degrees in Barnacle Love and Kicking the Sky De Sa’s storytelling questions the concept of Toronto the Good and the actual city of Toronto becomes a rhetorical space—the backdrop for a coming-of-age narration that empowers Antonio Rebelo with invention and agency and launches him toward adult life. (SCB)